Implementation of OTA in 90nm Technology with Bandgap Reference Application - R, Halesh M; S, Pavan; Tejaswini, Pappuru (Journal of Electronics and Informatics, 2023)
Operational Transconductance Amplifier (OTA) is the basic building block of Analog circuit with linear input/output characteristics. Because it associates closely linked parameters like noise and settling performance, the current design methodologies for two-stage OTAs frequently result in sub-optimal solutions. The study discusses the implementation of an Operational transconductance amplifier (OTA) with a bandgap reference (BGR) circuit and its importance in providing a stable and accurate reference voltage for various analog and digital circuits. The combination of OTA and BGR provides a stable and accurate reference voltage that can be used in various analog and digital circuits. OTAs are used to drive high capacitive loads. To scale the dimensions of Complementary Metal Oxide Semiconductor (CMOS) technology requires proportional scaling, also taking supply voltage into consideration. In addition to the simplicity and strong performance that the Band Gap Reference (BGR) achieves as a load for the OTA circuit, the architecture of OTA with BGR as load is easily adaptable to attain high accuracy. Because the performance of the used amplifier has a significant impact on the OTA’s performance, consideration must be given to the design and its architecture. Therefore, it is essential to carry out a comparison analysis in order to get the optimal results of the outputs of OTA having BGR as the load.
Keywords: OTA; Band gap Reference; CMOS; VLSI; VCO; VCF; SC